REPRESENTATION OF WOMEN IN THE 2019 ELECTION IN GUNUNGKIDUL DISTRICT - Realyta, Elfrida Bela; Rahmawati, Dian Eka (POLITICO, 2020)
Women's representation in the 2019 elections has increased. At this time the position of women in the world of politics is equal to men. The proof is that in each election period the participation of women has increased, from the elections in 2009, 2014, and until now the number of women's representation has increased. In Gunungkidul Regency, the representation of women in politicalparties has reached a percentage determined by the legislation, even exceeding the 30%quota.However, the electability of women in the parliamentary seats in Gunungkidul only reached22.22%. This study aims to analyze the representation of women in the 2019 elections in Gunugkidul Regency and its factors. There are supporting factors and obstacles in this study.This study uses a qualitative method. Data sources used are primary data and secondary data. Retrieval of data by interviewees through interviews and documentation. Based on the data analysis, it can be concluded that the representation of women in the 2019 elections in Gunungkidul Regency has increased in each election period starting in 2009, 2014, until 2019 at present. Although in 2019 it only reached a percentage level of 22.22% women's representation and has not reached 30%, this is already considered good. In addition, there are supporting factors which consist of family, social skills, availability of campaign costs, and parties. On the other hand there are also inhibiting factors namely the crisis of women's trust from the community, low political education, and minimal political costs. From the 7 aspects of these 2 factors, the authors have tested the field research with respondents who produced 71.4% of the factors according to experts the same as events in the field. There are 2 aspects which according to experts, are not felt in the lives of the respondents during the time leading up to the election. So there are new findings that occur in the field related to factors that affect the choice of women in the council seats.Â